LITERATUR REVIEW: ANALISIS KEMAMPUAN SHARED METACOGNITION SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA - Nurazisah Rahman; Aisyah Nursyam (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
Metacognitive ability plays an essential role in mathematical problem solving as it enables students to consciously plan, monitor, and evaluate their thinking processes. Along with the development of collaborative learning, metacognition has expanded beyond the individual domain to include a social dimension known as shared metacognition. This study aims to systematically examine the concepts, indicators, and research findings related to students’ shared metacognition in solving mathematical problems. This research employed a Systematic Literature Review (SLR) method guided by the PRISMA framework. Relevant articles were collected from national and international databases, selected based on inclusion and exclusion criteria, and analyzed thematically. The results indicate that shared metacognition plays a strategic role in enhancing the quality of mathematical problem solving through collective planning, monitoring, and evaluation processes. High-achieving students tend to demonstrate more complete metacognitive profiles, whereas students with moderate and low abilities experience difficulties, particularly at the evaluation stage. In addition, the role of expert students and the implementation of collaborative learning models such as Cooperative Script and Hybrid Project-Based Learning have been shown to support the development of shared metacognition. These findings highlight the importance of integrating shared metacognition into mathematics learning to foster students’ higher-order thinking skills. Keywords: shared metacognition; mathematical problem solving; collaborative learning; metacognition; HOTS